Effects of Health Counseling on the Level of Knowledge and Attitudes Regarding Sexual Health in AL-Huda MTs Students - Andi Suswani; Asdinar; Hamdana (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Abortion, pregnancy and sexually transmitted diseases are also a problem of adolescent sexual health in the world (WHO, 2015). This data shows that the number has increased every year. Increased sexual health problems also occur in cases of abortion, pregnancy and sexually transmitted diseases. The importance of knowledge about reproductive health, adolescents need to get enough information, so that they know what should be done and which should be avoided. Besides, with a good knowledge of sexual health, will form a positive attitude towards sexual health. This study aims to determine the effect of health education on the level of knowledge and attitudes about sexual health in MTs AL-Huda students. One group pretest-posttest design research design is the pre-experimental design type. A total population of 128 with a sample of 97 respondents employing purposive sampling and research instruments was a questionnaire. The results of univariate studies before health education for knowledge were 24 good (24.7%), 39 adequate (40.2%), 34 poor (35.1%) and attitudes of 36 positive (37.1%) and 61 negative ( 62.9%). After health education for knowledge, 62 were good (63.9%), 33 were sufficient (34.0%) and 2 were less (2.1%) while for attitudes namely, 78 were positive (80.4%) and 19 were negative (19, 6%), bivariate results with the Wilcoxon test (ρ = 0,000 <α = 0.05), it was concluded that there were significant differences between knowledge and attitudes before and after health education. It is recommended to improve the knowledge and attitudes of adolescents through health education, especially in maintaining and maintaining reproductive/sexual health.